If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -45x + 4 = -12 Reorder the terms: 4 + -45x = -12 Solving 4 + -45x = -12 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -45x = -12 + -4 Combine like terms: 4 + -4 = 0 0 + -45x = -12 + -4 -45x = -12 + -4 Combine like terms: -12 + -4 = -16 -45x = -16 Divide each side by '-45'. x = 0.3555555556 Simplifying x = 0.3555555556
| 3-2m+7m=5m-3m | | 131-(6x+12)=6(x+9)+x | | 3[b+7]=30 | | 3d-12=9 | | N-25=-25 | | 4x+2=3(x-3)+6 | | -3x-10=-50 | | 2(5-1.7*1.4)=15.1-7*1.4 | | D+4.7=2.8t(12) | | N-35=-18 | | 12x+13=4x+7 | | 2(4x+1)=90 | | 6+-6x=5x+61 | | N-25=18 | | 2(3x-1)-6x=-4 | | 3x+4x+5=-3 | | N-25= | | 3(7x+7)=252 | | (W+1)(2w-3)=5 | | 5=3k-2k | | Log(x)=9 | | 3x+4x+5=3 | | D+4.7=2.8t(7.4) | | 6(7m+3)= | | 3x+4x-5=3 | | -0.2x(-0.07)= | | 9b=4b-25 | | 7x+1=8x+16 | | 1650-25h=1325 | | 6x-3x=-6+5x | | 5(x-7+4)=34 | | -20x-8+7=-5 |